Implementation of Good Corporate Governance in the Placement of Indonesian Army Members in State Civil Apparatus Positions in Ministries/Institutions Case Study of the Ministry of State Secretariat - Sherlyta Devia Dongoran; Bobby W. Saputra (Riviera Publishing, 2025)
This study examines the implementation of Good Corporate Governance (GCG) principles in placing Indonesian National Armed Forces (TNI) members into civil servant positions in Ministries/Agencies, specifically at the State Secretariat Ministry. The research focuses on assessing the impact of this placement on employee performance, with GCG aiming to improve efficiency, transparency, and accountability in the process. Using a qualitative approach and case study method, the study involves in-depth interviews with relevant stakeholders and analysis of internal documents. The findings suggest that placing TNI members in civil servant roles can enhance discipline, efficiency, and effectiveness, bringing in specialized expertise. However, challenges such as cultural differences, lack of bureaucratic experience, and potential conflicts of interest also emerge. The study emphasizes the importance of consistent GCG implementation, including transparent selection processes, accountability in performance evaluations, and robust training programs. It also suggests mitigation strategies to address integration challenges, such as orientation programs, forming integration teams, and fostering greater awareness. The research concludes that while the policy has positive and negative aspects, practical GCG application and proper mitigation are key to maximizing benefits and minimizing risks